Cigarette Smoking is not a Risk Factor for Systemic Sclerosis - Chaudhary, Prateek (2011)
BACKGROUND: The role of cigarette exposure in susceptibility to systemic sclerosis (SSc) has not been previously studied. Our objective was to investigate the association of smoking with susceptibility to SSc in a large well-defined patient population. METHODS: We conducted a review of 1,379 SSc patients enrolled in the Scleroderma Family Registry and DNA Repository and/or the Genetics versus Environment in Scleroderma Outcome Study (GENISOS) cohort. Smoking history was obtained from chart review or via telephone interview. SSc patients were subsequently categorized as never smokers or ever smokers. SSc patients with available smoking data were matched 2:1 by age, gender, ethnicity and state of residence to controls using the Behavioral Risk Factor Surveillance System. RESULTS: The majority of cases were White (74.2%) with Latinos and Blacks representing 11.3% and 9.7%, respectively. Most patients had limited disease type (54%). For our comparative analyses, 621 patients were matched to controls. There was no significant difference in age, gender, ethnicity and SSc disease type between matched versus unmatched patients. The majority of patients had never smoked (57%), while 43% of patients were ever smokers. The SSc patients did not differ in their smoking behavior from controls (p=0.842, OR: 1.020, 95% CI: 0.839–1.240). Anti-topoisomerase positive patients were more likely to be never smokers (p=0.049, OR=0.648, 95% CI=0.421–0.998) whereas no such association was found with the anti-centromere and anti-RNA Polymerase antibodies. CONCLUSION: Unlike in rheumatoid arthritis, smoking does not confer a risk for development of SSc, though it may impact disease severity.